Exploring Ethnomathematics in Batak Toba Carvings for Locally-based Mathematics Teaching Material - Ditasona, Candra (Journal of Education Reseach and Evaluation, 2023)
As one of the traditional ornaments of the Batak Toba tribe, "gorga" carries philosophical meaning and serves to embellish the decoration of traditional houses. The gorga motif has its own distinctive characteristics, with closely arranged patterns and symmetrical designs. This indicates the presence of mathematical aspects within these carved gorga patterns. This research aims to analyze the symmetries embedded in the gorga motifs that can be utilized as locally-based mathematics teaching material. The study is conducted by exploring various gorga motifs and analyzing their types of symmetry. The research is employing an ethnographic research approach. Data is collected through observing buildings adorned with gorga motifs, studying literature, and conducting interviews with gorga carvers. Qualitative data analysis can be started with data reduction, data presentation, drawing conclusions and verification. The research findings reveal the existence of seven types of symmetry obtained from all gorga motifs. These symmetry types include translation symmetry, glide reflect symmetry, vertical symmetry, rotation 180° symmetry, vertical and  rotation 180° symmetry, horizontal symmetry, and vertical and horizontal symmetry.